Brain functional connectivity during and after imagery of gaming and alternative leisure activities in patients with internet gaming disorder. (16th February 2022) - Kim, Soo-Jeong; Eom, Hyojung; Jung, Young Hoon; Kim, Min-Kyeong; Kim, Eunjoo; Kim, Jae-Jin
Highlights: Effects of imageries of gaming and alternative activities on connectivity were examined. Seed-based functional connectivity during and after the tasks were analyzed. Caudate-parahippocampal and putamen-orbitofrontal connectivity increased during gaming. Reward pathway-precuneus connectivity increased in post-gaming. Both during-gaming and post-gaming network connectivities are important in IGD. Abstract: Background: The effect of gaming cue exposure on brain activity in patients with internet gaming disorder (IGD) has been investigated a lot, but the effect on brain connectivity has not. This study aimed to investigate the effects of imageries of gaming and alternative leisure activities on functional connectivity during the during-task and post-task states in patients with IGD. Methods: Twenty-nine patients and 20 healthy controls were scanned in the 6-min states before, during, and after the imagery tasks for gaming and alternative leisure behaviors using fMRI. Seed-based functional connectivity during and after the tasks were analyzed. The seeds were the nucleus accumbens (NAcc), ventral tegmental area (VTA), caudate, putamen, anterior cingulate cortex (ACC), and posterior cingulate cortex. Results: The group-by-state interaction effects for the during-tasks were found in caudate-, putamen-, and ACC-based connectivity, whereas those for the post-tasks were shown only in NAcc-based connectivity. In particular, patients showed that caudate-right parahippocampal gyrus connectivity and putamen-right orbitofrontal cortex connectivity increased during gaming and decreased during alternative, whereas NAcc-right precuneus connectivity decreased at baseline, increased in post-gaming, and were not different in post-alternative. Conclusion: Differences in during-task connectivity of the habit/motor and salience networks and post-task resting-state connectivity of the reward and limbic networks between the two imagery tasks may differ between the groups. In the treatment of IGD, when these network connections are reactive to alternative leisure activity, just as to gaming activity, they seem to be freed from gaming addiction.